2019
DOI: 10.1007/s00586-019-06078-y
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar junction orientation: its impact on thoracic kyphosis and sagittal alignment in both asymptomatic volunteers and symptomatic patients

Abstract: Purpose The thoracolumbar junction (TLJ) has not been explored in regard to its contribution to global sagittal alignment. This study aims to define novel sagittal parameters of the TLJ and to assess their roles within global sagittal alignment. Methods Included for cross-sectional, retrospective analysis were asymptomatic volunteers and symptomatic patients who had undergone operation for adult spinal deformity. Unique sagittal parameters of the TLJ were measured using the midline of the T12-L1 disk space: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Among them, TLS most highly correlated with ODI score (r = 0.374, p = 0.002). Multivariate logistic regression analysis showed that TLS greater than -3.5°, which is the mean value in patients with PDSI who require surgical treatment due to clinical symptoms, 11 was a predicting factor for PDSI aggravation (p = 0.034; confidence in- terval, 1.173-63.61; odds ratio, 8.636). A BMI greater than 25 kg/m 2 , which is the criterion for overweight; an SVA greater than 9.5 cm, which is the criterion for marked deformity 8 ; and a T1PA greater than 30° were not significant predictors for PDSI aggravation (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among them, TLS most highly correlated with ODI score (r = 0.374, p = 0.002). Multivariate logistic regression analysis showed that TLS greater than -3.5°, which is the mean value in patients with PDSI who require surgical treatment due to clinical symptoms, 11 was a predicting factor for PDSI aggravation (p = 0.034; confidence in- terval, 1.173-63.61; odds ratio, 8.636). A BMI greater than 25 kg/m 2 , which is the criterion for overweight; an SVA greater than 9.5 cm, which is the criterion for marked deformity 8 ; and a T1PA greater than 30° were not significant predictors for PDSI aggravation (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…PDSI is understood as the cumulative result of degenerative changes and the natural progression of aging. 11,17 In a longitudinal study of age-related changes in sagittal spinal alignment in 237 individuals over a 4-year period, Oe et al 18 reported that SAPs deteriorated with age, including SS, PT, LL, T1 slope, cervical lordosis, and SVA in the seventh-decade female group. Many elderly individuals experience mild sagittal imbalance, but PDSI does not deteriorate in all individuals with aging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations